Sequestosome 1 Deficiency Delays, but Does Not Prevent Brain Damage Formation Following Acute Brain Injury in Adult Mice - Sebastiani, Anne; Gölz, Christina; Sebastiani, Philipp G.; Bobkiewicz, Wiesia; Behl, Christian; Mittmann, Thomas; Thal, Serge C.; Engelhard, Kristin (Frontiers in Neuroscience, 2017)
Abstract Neuronal degeneration following traumatic brain injury (TBI) leads to intracellular accumulation of dysfunctional proteins and organelles. Autophagy may serve to facilitate degradation to overcome protein debris load and therefore be an important pro-survival factor. On the contrary, clearing may serve as pro-death factor by removal of essential or required proteins involved in pro-survival cascades. Sequestosome 1 (SQSTM1 / p62) is a main regulator of the autophagic pathway that directs ubiquinated cargoes to autophagosomes for degradation. We show that SQSTM1 protein levels are suppressed 24 hours and by trend 5 days after trauma. In line with these data the expression of Sqstm1 mRNA is reduced by 30% at day 3 after and stays depressed until day 5 after injury, indicating an impaired autophagy post controlled cortical impact (CCI). To determine the potential role of SQSTM1-dependent autophagy after TBI, mice lacking SQSTM1 (SQSTM1-KO) and littermates (WT) were subjected to CCI and brain lesion volume was determined 24 hours and 5 days after insult. Lesion volume is 17% smaller at 24 hours and immunoblotting reveals a reduction by trend of cell death marker αII-spectrin cleavage. But there is no effect on brain damage and cell death markers 5 days after trauma in SQSTM1-KO compared with WT. In line with these data neurofunctional testing does not reveal any differences. Additionally, gene expression of inflammatory (Tnf-α, iNos, Il-6, and Il-1β) and protein degradation markers (Bag1 and Bag3) were quantified by real-time PCR. Protein levels of LC3, BAG1, and BAG3 were analyzed by immunoblotting. Real-time PCR reveals minor changes in inflammatory marker gene expression and reduced Bag3 mRNA levels 5 days after trauma. Immunoblotting of autophagy markers LC3, BAG 1, and BAG3 does not show any difference between KO and WT 24 hours and 5 days after TBI. In conclusion, genetic ablation of SQSTM1-dependent autophagy leads to a delay but shows no persistent effect on post-traumatic brain damage formation. SQSTM1 therefore only plays a minor role for secondary brain damage formation and autophagic clearance of debris after TBI. Key Words: traumatic brain injury, protein degradation, autophagy, SQSTM1, p62, BAG3, mouse model